Present‐Day Patagonian Dust Emissions: Combining Surface Visibility, Mass Flux, and Reanalysis Data. Issue 16 (11th August 2021) - Cosentino, N. J.; Gaiero, D. M.; Lambert, F.
Abstract: The magnitude of the climatic forcing associated with mineral dust aerosols remains uncertain due in part to a lack of observations on dust sources. While modeling and satellite studies provide spatially extensive constraints, they must be supported by surface‐validating dust monitoring. Southern South America is the main dust source to the southern oceans (>45°S), a region of low biological productivity potentially susceptible to increased micronutrient fertilization through dust deposition, as well as one of the main dust sources to Antarctica, implying long‐range transport of dust from Patagonia and potentially affecting snow cover albedo. We present multiyear time series of dust‐related visibility reduction (DRVR) and dust mass flux in Patagonia. We find that local DRVR is partly controlled by long‐term (i.e., months) water deficit, while same‐day conditions play a smaller role, reflective of water retention properties of fine‐grained dust‐emitting soils in low‐moisture conditions. This is supported independently by reanalysis data showing that large‐scale dust outbreaks are usually associated with anomalously high long‐term water deficit. By combining visibility data, surface dust sampling, and particle dispersion modeling, we derive regional dust emission rates. Our results suggest that the inclusion of long‐term soil hydrologic balance parameterizations under low‐moisture conditions may improve the performance of dust emission schemes in Earth system models. Key Points: Large‐scale Patagonian dust outbreaks are linked to anomalously high surface winds during cyclonic cold fronts and long‐term water deficit Long‐term water deficit also controls local dust emissions and reflects water retention properties of fine‐grained, low‐moisture sources Dust emission rates of 1.4 ± 0.7 Tg yr −1 (2009–2019, ∼54°S) and 6.2 ± 2.5 Tg yr −1 (2004–2005, ∼49°S) were derived in southern Patagonia